Vocational Technical Education and Training for Self-Reliance: Towards National Development - Nwogu, Prince Opurum; Nwanoruo , Christopher, C. (Mediterranean Journal of Social Sciences, 2011)
This paper criticized an educational system which was faulty from the onset and stressed that vocational technicaleducation and training is that form of Education that leads to acquisition of practical skills, which will enable an individual to begainfully employed in a chosen occupation to become self-reliant, in order to contribute to overall national development.However, a detailed analysis of the concept of vocational technical education and national development were greatly examined.Challenges facing vocational technical education and training for self-reliance and national development were pointed out.Some of which are: the lack of skilled man- power, inadequate training facilities and equipment, lack of follow-up and continuityin government policies, poor remuneration of vocational and technical teachers, lack of entrepreneurship education in vocationaltechnical education and training and poor emphasis on the practical aspect of vocational technical education and training.Finally, one of the major recommendations is that, both the government and the non government organizations (NGOs) shouldpay serious attention to entrepreneurship development in technical vocational education and training by putting its priorities rightand releasing funds adequately for proper development of individuals to become self-reliant and contribute to nationaldevelopment.